2006
DOI: 10.4269/ajtmh.2006.74.81
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of the Leishmania Species in the Guianan Ecoregion Complex

Abstract: Abstract. In the Guianan ecoregion complex, at least seven Leishmania species belonging to both the L. (Leishmania) Saf' janova, 1982 and L. (Viannia) Lainson and Shaw, 1987 sub-genera are causative agents of American visceral leishmaniasis, mucocutaneous leishmaniasis, and cutaneous leishmaniases, including localized and diffuse forms. They are mostly sylvatic species subjugated to their own specific Lutzomyia sand fly vectors and to particular wild mammalian reservoir hosts of the dense rain forest. Origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
1
15

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(105 citation statements)
references
References 182 publications
(268 reference statements)
4
85
1
15
Order By: Relevance
“…This might be explained by the methodology used in our work and also the higher levels of deforestation and degraded living conditions in our studied area. Notably, all infected sandflies were found in the peridomicile areas where we could observe a large number of animals, mainly chickens and dogs (Moreira et al 2003, Rotureau 2006.…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by the methodology used in our work and also the higher levels of deforestation and degraded living conditions in our studied area. Notably, all infected sandflies were found in the peridomicile areas where we could observe a large number of animals, mainly chickens and dogs (Moreira et al 2003, Rotureau 2006.…”
Section: Discussionmentioning
confidence: 99%
“…In neighboring French Guyana L. guyanensis is the main cause of CL, although cases caused by L. braziliensis are occasionally encountered. 12 Until recently it was believed that L. guyanensis was the only species prevailing in Suriname. 13 Because of the increasing travel between Suriname and neighboring countries, like Brazil and French Guyana, it is possible that other Leishmania species, such as L. braziliensis, have been imported.…”
Section: Resultsmentioning
confidence: 99%
“…Although it has previously been suggested that Th. ubiquitalis does not exhibit high levels of anthropophilic behavior under field conditions (28) Nyssomyia umbratilis has been identifi ed as the main vector of L. (V.) guyanensis in northern Brazil, particularly in the Guianan ecoregion complex (31) . The fi ndings of the present study suggest that Ny.…”
Section: Discussionmentioning
confidence: 99%